Being Howard Jacobson: An Introduction. Issue 2 (1st September 2022) - Cheyette, Bryan
Abstract: Howard Jacobson (1942–) has been the leading Jewish writer in Britain for nearly four decades. He remains at the height of his powers with the recent publication of his memoir, Mother's Boy: A Writer's Beginnings (2022) which is referred to throughout this introduction. I will return to Jacobson's first novel, Coming from Behind (1983), to show how it relates to his 'golden' period which is the focus of the articles in this Special Issue. Novels produced during this period include: The Mighty Walzer (1999), Kalooki Nights (2006), The Finkler Question (2010), J: A Novel (2014) and Shylock Is My Name (2016). Jacobson's growing confidence – moving between the individual and the collective, between comedy and tragedy, and between realism and experimentalism – will be at the heart of the introduction.